Neurocognitive Dysfunction and Criminal Liability: Integrating Neuroscience, Legal Theory, and Islamic Thought - Rafika Nur; Azwad Rachmat Hambali; Ridwanto Igirisa; Handar Subhandi Bakhtiar; Ahmad Fakhrurrazi Mohammed Zabidi (Contemporary Issues on Interfaith Law and Society, 2025)
This article examines the relationship between neurocognitive dysfunction, criminal behaviour, legal theory, and Islamic thought, with particular attention to the neurobiological foundations of moral decision-making and criminal responsibility. Employing an interdisciplinary normative approach that integrates cognitive neuroscience, criminal law theory, moral philosophy, and Islamic jurisprudence, this study analyses how neurobiological dysfunctions especially those affecting the prefrontal cortex and amygdala may influence impulse control, moral judgement, and antisocial conduct. Drawing exclusively on a critical review of scholarly literature, judicial decisions, and normative legal sources, the article explores the implications of neuroscientific findings for concepts of free will, moral agency, and criminal liability. The analysis demonstrates that while neuroscientific evidence has the potential to inform sentencing mitigation and rehabilitative strategies, its application raises significant ethical and legal challenges, particularly concerning biological determinism, evidentiary reliability, and procedural fairness. From an Islamic legal perspective, sound intellect (‘aql) constitutes the foundation of taklīf (legal responsibility), yet Islamic jurisprudence recognises circumstances in which responsibility may be diminished or removed, in accordance with the principles of raf‘ al-ḥaraj and maqāṣid al-sharī‘ah. The article argues that the absence of clear procedural standards and limited doctrinal integration of neuroscience within criminal justice systems particularly in Indonesia and Malaysia necessitates a more coherent normative framework. Ultimately, this study proposes a holistic and ethically grounded approach to criminal justice reform that integrates neuroscientific insights with legal principles and religious values, aiming to enhance proportionality, procedural justice, and human dignity.